SKRINING SIFILIS MENGGUNAKAN Treponema pallidum RAPID PADA PEKERJA MIGRAN INDONESIA DI KABUPATEN BANYUMAS - Fadhil Rabbani; Indah Sulistiyawati (Universitas Lambung Mangkurat, 2026)
Syphilis is a sexually transmitted infection (STI) caused by Treponema pallidum subspecies pallidum that continues to pose a significant public health challenge, particularly among groups such as Indonesian migrant workers (PMI). Early detection is essential in preventing transmission and ensuring appropriate treatment. This study aimed to determine the prevalence of syphilis among Indonesian migrant workers using the Treponema pallidum Rapid Test (TP-Rapid) at a health facility in Banyumas Regency. The diagnostic procedure was conducted in three stages such as pre-analytic, analytic, and post-analytic. A quantitative descriptive method with a cross-sectional approach was employed involving 160 Indonesian migrant workers undergoing pre-departure health screening. Blood samples were collected and tested using the TP-Rapid method, which offers rapid, sensitive, and specific detection of T. pallidum antibodies. Results indicated that 10 out of 160 samples (6,25%) was reactive for syphilis, while 150 samples (93,75%) were non-reactive. Despite the relatively low prevalence, the findings underscore the necessity of routine syphilis screening. The TP-Rapid test was found to be a practical diagnostic tool due to its simplicity, rapid turnaround time, and reliability in identifying syphilis seroreactivity. These results highlight the importance of integrating early syphilis detection into mandatory health screenings for migrant workers to mitigate potential transmission and safeguard both individual and public health.